Phosphorene-Supported Au(I) Fragments for Highly Sensitive Detection of NO - Huimin Guo; Yuhan Liu; Xin Liu (Molecules)
The fabrication and application of single-site heterogeneous reaction centers are new frontiers in chemistry. Single-site heterogeneous reaction centers are analogous to metal centers in enzymes and transition-metal complexes: they are charged and decorated with ligands and would exhibit superior reactivity and selectivity in chemical conversion. Such high reactivity would also result in significant response, such as a band gap or resistance change, to approaching molecules, which can be used for sensing applications. As a proof of concept, the electronic structure and reaction pathways with NO and NO2 of Au(I) fragments dispersed on phosphorene (Pene) were investigated with first-principle-based calculations. Atomic-deposited Au atoms on Pene (Au1-Pene) have hybridized Au states in the bulk band gap of Pene and a decreased band gap of 0.14 eV and would aggregate into clusters. Passivation of the Au hybrid states with -OH and -CH3 forms thermodynamically plausible HO-Au1-Pene and H3C-Au1-Pene and restores the band gap to that of bulk Pene. Inspired by this, HO-Au1-Pene and H3C-Au1-Pene were examined for detection of NO and NO2 that would react with -OH and -CH3, and the resulting decrease of band gap back to that of Au1-Pene would be measurable. HO-Au1-Pene and H3C-Au1-Pene are highly sensitive to NO and NO2, and their calculated theoretical sensitivities are all 99.99%. The reaction of NO2 with HO-Au1-Pene is endothermic, making the dissociation of product HNO3 more plausible, while the barriers for the reaction of CH3-Au1-Pene with NO and NO2 are too high for spontaneous detection. Therefore, HO-Au1-Pene is not eligible for NO2 sensing and CH3-Au1-Pene is not eligible for NO and NO2 sensing. The calculated energy barrier for the reaction of HO-Au-Pene with NO is 0.36 eV, and the reaction is about thermal neutral, suggesting HO-Au-Pene is highly sensitive for NO sensing and the reaction for NO detection is spontaneous. This work highlights the potential superior sensing performance of transition-metal fragments and their potential for next-generation sensing applications.